Pemanfaatan Teknologi Pengelolaan OPT Tanaman Sayuran Berbahan Baku Ramah Lingkungan Di Kanagarian Paninjauan Kabupaten Tanah Datar - Ujang Khairul; Reflin Reflin; Arneti Arneti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2016)
Activity of use management technologogy for pest and plant disease control on vegetables based environment friendly in nagari Paninjauan Kabupaten Tanah Datar has been carried out from June to November 2014. This activity aims to improve farmers knowledge about the diseases attack of vegetables and know how to manage the disease using biopesticide and botanic biopesticide, These activities include: Counseling and training, and evaluation. Results of monitoring the level of disease in vegetable crops is known that those plants attacked by pest and pathogens e.i, soft rot (cabbage), anthracnosa, bacterial wilt and leaf spot (chili), tuber rot ( carrots) and bacterial leaf blight and Alternaria spots (onion leaves). Attack rate ranged between 16 – 20% for disease and 15 – 30% for pest. From the activities can be take several conclusions: (1) Extent of disease in vegetable crops in this area is high, (2) The farmers do not yet understand the causes of pest and plant disease (pathogens) that attack their vegetable crops, (3) The farmers do not understand the methods of disease control using biopesticide and botanic biopesticide, (4) The extension and field practice, have improved farmers' knowledge about the management of vegetable diseases using biopesticides and botanic biopesticide